Ending an elite sports career: Case report of behavioral activation applied as an evidence-based intervention with a former Olympic athlete developing depression - Lundqvist, C. (The Sport Psychologist, 2020)
This case report described the use of behavioral activation when a former Olympic athlete developed depression after career termination. Four sessions were conducted, one session each week, followed by a boost session 1 month later. In Session 1, the former Olympic athlete displayed mild-to-moderate depression with anxiety and a low quality of life (Montgomery-Åsberg Depression Rating Scale = 21; Generalized Anxiety Disorder-7 Scale = 17; Brunnsviken Brief Quality of Life Scale = 44). By Session 3, the Olympic athlete no longer met the diagnostic criteria for clinical depression or anxiety (Montgomery-Åsberg Depression Rating Scale = 2; Generalized Anxiety Disorder-7 Scale = 7) and the quality of life was improved (Brunnsviken Brief Quality of Life Scale = 60). Follow-up assessments 1-year posttreatment confirmed that the former Olympic athlete continued to improve (Montgomery-Åsberg Depression Rating Scale = 0; Generalized Anxiety Disorder-7 Scale = 0; Brunnsviken Brief Quality of Life Scale = 96). This case report discusses the benefits of proactive support to elite athletes and the use of established clinical psychological treatments, for example, behavioral activation, when athletes develop health-related conditions.